PROHIBITION OF GIFT ACCEPTANCE IN HADITH: SANAD CRITICISM AND PUBLIC ETHICS IMPLICATIONS - Purnomo, Sugiyono; Supian, Aan; Johendra, Meki (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
In society, people often give gifts. Many people do not understand the gifts that are forbidden and allowed in Islam. Using the thematic hadith study method, this study examines hadiths related to the prohibition of receiving gifts based on the words of the Prophet PBUH. This study uses thematic literature studies. Data collected from primary and secondary sources were then analyzed using content and documentary analysis techniques. Takhrij is also done to collect relevant hadith and assess its quality using the method of sanad criticism. The results of the study show that the nine books of hadith (Kutubus Tis'ah) contain thirteen narrations that are categorized into five main themes that prohibit accepting prizes: (1) it is forbidden to accept prizes in competitions that contain betting or gambling, (2) it is forbidden to receive prizes during ihram related to the ethics of Hajj and Umrah, (3) it is forbidden to accept gifts in the form of goods that are forbidden to be used to control worldly pleasures, (4) it is forbidden for officers to receive gifts to prevent corruption and conflicts of interest, and (5) it is forbidden to accept gifts in the form of wages in religious teachings that should be given to people who perform the Hajj Of the five main hadiths studied, four are of saheeh quality, and one is of hasan quality. This research emphasizes how important it is to understand the concept of reward in Islam to ensure that it does not conflict with justice and religious moral values.